The Role of Microeconomic Analysis in Decision Making Pricing in the Retail Industry - Kholilul Kholik; Suendrizal (Yayasan Multidimensi Kreatif, 2025)
Proper pricing is one of the key factors in achieving success in the retail industry. In this context, microeconomic analysis plays an important role in aiding efficient and profitable pricing decision-making. This study aims to analyze how microeconomic concepts, such as price elasticity, cost theory, and market structure, affect the pricing decisions made by retail companies. Using a qualitative approach and case studies on some of the leading retail companies, the study identified a variety of factors considered in pricing, including changes in demand, production costs, as well as the characteristics of the markets in which the company operates. The results show that retail companies that apply the principle of price elasticity tend to be able to adjust prices better according to consumer demand, while companies operating in oligopoly markets are often more cautious in setting prices to maintain competitiveness. In addition, production costs and fixed costs also influence pricing decisions, with companies tending to raise prices when operating costs increase. The study concludes that a deep understanding of microeconomic analysis can improve the effectiveness of pricing decision-making, which in turn will improve the competitiveness and profitability of retail companies.